(5x)=(3x+13)

Simple and best practice solution for (5x)=(3x+13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x)=(3x+13) equation:


Simplifying
(5x) = (3x + 13)

Reorder the terms:
(5x) = (13 + 3x)

Remove parenthesis around (13 + 3x)
(5x) = 13 + 3x

Solving
(5x) = 13 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
(5x) + -3x = 13 + 3x + -3x

Combine like terms: (5x) + -3x = 2x
2x = 13 + 3x + -3x

Combine like terms: 3x + -3x = 0
2x = 13 + 0
2x = 13

Divide each side by '2'.
x = 6.5

Simplifying
x = 6.5

See similar equations:

| -3.3(y+8)-2.5y= | | -9=9(h-2) | | 3x^2+30x-12=0 | | (3x-9)+(x+7)=90 | | -y+16+6y=44 | | z+10=z-5 | | 2y^2=-16y | | (2x+6)(3x+10)=0 | | -2x-8=4x+16 | | 3z^2-7z+4=0 | | 5(-1)-2= | | 176-6x=39x-21 | | 0.45(5-0.4n)=-3.2 | | 5x-2=-2x-9 | | 3-18+8x=67 | | 2(-3+4y)=-6 | | 6m/5=24 | | -8*x+3=251 | | 15y^2+46y+16=0 | | 17p-3=48 | | 4x+2=2x+24 | | x^4+3x^2-54=0 | | 4w^2=-28w | | =3ln(8) | | 7t-8=4t-2 | | 3x-8=10-3x | | 5n(2n+8)=0 | | -5x+4=-40+6x | | (2x^3)x(8x^8)= | | 9x^2+2x=10x | | 6s-10=-3x+8 | | -15=-30 |

Equations solver categories